AN ANALYSIS OF DEIXIS IN RAJA CAMPUR SARI OF DIDI KEMPOT’S SONG - Jimmi Arwy; Sortha Silitonga (LINGUISTICA, 2013)
ABSTRACT This study deals with the types of deixis in Raja Campur Sari of Didi Kempot’s Song. The objective of this study are to describe the types of deixis that are used in Raja Campur Sari of Didi Kempot’s song, finding out the dominant types, and finding out why the type of deixis is dominantly used in Raja Campur Sari of Didid Kempot’s Song. This study applied descriptive qualitative method. The data of this study were taken from VCD of Raja Campur Sari of Didi Kempot’s song. There were 10 song lyrics taken as the samples. The findings of this study show that there are five types of deixis were found in Raja Campur Sari of Didi Kempot’s song, there are person deixis 33.7%, spatial deixis 16.6%, temporal deixis 16.4%, discourse deixis 20.3% and social deixis 13%. The most dominant type of deixis found is person deixis. Person deixis is dominantly used because hemostly wrote her own experiences into the song lyrics. Keyword: Pragmatics, Deixis, Song